(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
Indonesia has a diversity of cultures, hospitality, and people with good ethics. Moral problems still occur, namely corruption, collusion, nepotism, promiscuity and drug abuse, sexual harassment, theft, and murder. The Indonesian nation experienced moral degradation. Moral Education refers to the concept of Moral Behavior. Ethical behavior is grouped into three parts: Moral Attitudes, Moral Feelings, and Moral Thoughts. Moral education is very dependent on how to educate parents, associations, and the community environment. This study aims to analyze moral education from the perspective of religion, philosophy, psychology, and sociology. This study uses the literature review method. The process is carried out by analyzing statements, opinions, and arguments in various literature. The results of the analysis are mapped to the theme of moral education, study aspects include religion, philosophy, psychology, and sociology, as well as discussions in the form of attitudes, feelings, and thoughts. The research results show that moral education from a religious perspective plays a role in the formation of individual moral feelings. The philosophical perspective plays a role in the way of thinking that puts forward moral values. The psychological perspective plays a role in the aspects of feeling and thinking. The sociological perspective interacts with moral behavior.